ALTERATIONS OF SERUM CALCIUM, PHOSPHORUS, MAGNESIUM, AND COPPER IN HYPERTHYROIDISM PATIENTS: A CASE–CONTROL STUDY: Mineral metabolism in Hyperthyroidism - ATHOKPHAM, DIANA; MOHANTY, SHRABANI; BHARATKUMAR PINNELLI, VENKATA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to estimate the levels of serum calcium, phosphorus, magnesium, and copper in hyperthyroid cases and to correlate each of the parameter with serum T3, T4, TSH, FT3, and FT4, respectively. Methods: The study was conducted on 60 newly confirmed hyperthyroid cases based on the thyroid profile and 60 euthyroid cases were recruited as controls. Blood samples were collected from all these subjects and estimation of serum T3, T4, TSH, FT3, FT4, calcium, phosphorus, and magnesium was done by autoanalyzer method. Serum copper was measured by modified spectrophotometric micro-method using guanidine hydrochloride and bathocuproine disulfonate disodium salt. The statistical analysis was done by paired test and Pearson’s correlation. Results: Study results in hyperthyroid cases show mean serum calcium and copper levels were significantly (p<0.001) increased, serum phosphorus levels were significantly (p<0.001) decreased when compared to euthyroid. However, there was no significant change in magnesium when compared with euthyroid controls (p=0.556). We also found a significant positive correlation among serum Ca versus T3, T4, FT3, and FT4. A negative correlation with serum Ca versus TSH as observed. We also found significant positive correlation between serum phosphorus with TSH and significant negative correlation of phosphorus with T3, T4, FT3, and FT4. No suggestive significant correlation was found between serum Mg with T3, T4, TSH, FT3, and FT4 and serum copper with serum T3, T4, TSH, FT3, and FT4. Conclusion: The present study has shown that metabolism of minerals is altered in hyperthyroid cases. Impaired metabolism of calcium, phosphorus, magnesium, and copper can lead to various metabolic disorders. Estimation of serum calcium, phosphorus, magnesium, and copper may be helpful in better management to prevent further complication and can be used as diagnostic or prognostic aid in patients with hyperthyroidism along with other biochemical parameters.